Propuesta para elaboración de abono a partir de compostaje teniendo en cuenta la inclusión de una mezcla de microorganismos en el proceso. (2022)
This degree project sought to evaluate the composting production process using residential organic waste and studied how the intervention of a mixture of microorganisms influences the process, providing an alternative to produce organic fertilizer and contribute to the good use of the environment. In the first place, we started from a study about the production of composting without the addition of microorganisms, taking into account the physicochemical characteristics and the adequate operating conditions, carrying out a production on a laboratory scale where each of them is measured. Then, the microorganisms that favor the degradation of the raw material were selected based on a bibliographic review of 20 articles where the way of inoculation of each one was studied and their influence on the process was observed, analyzing their properties.